1996
DOI: 10.1007/bf00194093
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization characteristics of LiNbO3 derived from sol-gel

Abstract: A sol-gel process for lithium niobate using lithium ethoxide and niobium ethoxide precursors was investigated. Nitric acid and acetic acid were used as catalysts, respectively. The crystallization characteristics of the sol-gel-derived lithium niobate is influenced intensively by catalysts, and the crystallization of LiNbO3 from the nitric-acid-catalyzed sol-gel can occur at a low temperature near to 300~

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Chen et al reported that Ba(Mg 1/3 Ta 2/3 )O 3 ceramics had a bulk density of 0.98 theoretical density, the value was obtained by adding NaF as sintering aid [8]. Tochi Ta 2/3 )O 3 ceramics decreased with the proportion of Ba 5 Ta 4 O 15 , and the dielectric constants (ε r ) were insignificantly changed [10,11].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chen et al reported that Ba(Mg 1/3 Ta 2/3 )O 3 ceramics had a bulk density of 0.98 theoretical density, the value was obtained by adding NaF as sintering aid [8]. Tochi Ta 2/3 )O 3 ceramics decreased with the proportion of Ba 5 Ta 4 O 15 , and the dielectric constants (ε r ) were insignificantly changed [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…Many efforts had been investigated to improve the sinterability of Ba(Mg 1/3 Ta 2/3 )O 3 ceramics at lower temperatures [8,9]. Chen et al reported that Ba(Mg 1/3 Ta 2/3 )O 3 ceramics had a bulk density of 0.98 theoretical density, the value was obtained by adding NaF as sintering aid [8].…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic method used in this work is based on a combination of ethoxides and hydrogen peroxide (H 2 O 2 ) and is essentially very similar to those used in the last 3 or 4 decades. , Examples of using only peroxides are also known . Even though the sol–gel method is considered to be expensive and time-consuming, it is believed to be as one of the most attractive ways to obtain pure and single-crystalline materials.…”
mentioning
confidence: 99%
“…As a result, a clear yellowish solution was produced. It should be mentioned that, in almost all procedures reported so far, before drying, the obtained LiOEth/NbOEth mixtures were hydrolyzed by diluted aqueous alcohol, 6 ammonia, 18 or acid 12 solutions. In the present work, the obtained clear and unhydrolyzed solution was dried as soon as both components were dissolved (after ∼10 min).…”
mentioning
confidence: 99%